Modelos CAPM e CCAPM aplicados ao mercado imobili??rio de S??o Paulo e Rio de Janeiro - Severino, L??lian Santos Marques (2016)
This study aims to analyze the behavior of the real estate market in the Brazilian cities of S??o Paulo and Rio de Janeiro from 2008 to 2016 as seen through the analysis of monthly pricing data for both sales and rental markets, apparent consumption, stock of properties, and market return (IBOVESPA). Two models were estimated, the first, the CAPM, aimed at analyzing how return from investment in housing in both cities compared to the market return (IBOVESPA). The second model, the CCAPM was modified to suit the presence of preference for ownership of property. This study concludes that regarding the change-over of the return rates in Rio de Janeiro and S??o Paulo, investment in the housing market in both cities is negatively affected by the change-over of the return in investments on the whole stock market. Moreover, when we include the consumption in the pricing model, there is an intertemporal discount factor for consumption of roughly 0,98 per month for both cities, which confirms that Brazilian real estate buyers are more impatient than their American counterparts, and that the percentage of their income spent on consumption and investment in housing varies from one city to another.